La consejería en los programas de planificación familiar (1996)
ABSTRACT: The counselling in family planning is a process of interpersonal communication in which a person assists another person to take a free and responsible decision in order to behave as well. The Colombian Law 100 of 1993 framed into the Basic Assistance Plan (P.B.A) formally states the counselling of family planning as one of the basic service to the users in the reproductive age. This situation demands from the professional, in planning methods, and to adapt the concepts and operations of the process of the counselling of family planning. This garantees to the users their rights of choice and premium quality of the services they use.